UNSUPERVISED MACHINE LEARNING FOR SEISMIC ANOMALY DETECTION: LOCAL OUTLIER FACTOR ALGORITHM TO INDONESIAN EARTHQUAKE DATA - Gregorius Airlangga (LPPM Universitas Bina Bangsa, 2023)
Indonesia's location on the